Application of linear gradient elution in countercurrent chromatography for the separation of triterpenoid saponins from the roots of Pulsatilla koreana Nakai. Issue 13 (19th June 2017) - Lee, Kyoung Jin; Song, Kwangho; Song, Da Young; Kim, Yeong Shik
Abstract : A linear gradient elution method using countercurrent chromatography was developed for the separation of four triterpenoid saponins from the roots of Pulsatilla koreana Nakai, including hederacolchiside E, which is responsible for the neuroprotective activity of this plant. The target fraction was obtained by 80% methanol elution of solid phase column chromatography. The partition coefficients of the target compounds were very different, which means they are difficult to separate with a single biphasic solvent system. Several important parameters for gradient elution, such as addition of alcohol content to the solvent system, starting point of the second mobile phase, and the time for the gradient change were logically determined and optimized. Four triterpenoid saponins could ultimately be separated, analyzed by high‐performance liquid chromatography, and their structures were identified by comparing the mass spectra and NMR spectra with the literature data. The compounds and yields were: hederasaponin B (1 ; 21.3 mg/100 mg), hederacolchiside E (2 ; 19.8 mg/100 mg), cernuoside A (3 ; 18.4 mg/100 mg), and cernuoside B (4 ; 17.3 mg/100 mg). Gradient‐elution countercurrent chromatography allows the effective separation of compounds with a wide polarity range.